Relation between Risk Factors of Pyoderma and Pyoderma Incidence - Depari, Lila Indria; Sugiri, Unwati; Hamied, Lola Ilona Fuad Abdul (Althea Medical Journal, 2016)
Background: Pyoderma is a purulent bacterial infection of the skin. In developing countries, pyoderma is the most common skin disease in children. Pyoderma attacks male more often than female. Factors influencing pyoderma are low socioeconomic level, low education, low personal hygiene and unhygienic house. This study was conducted to assess the relation between risk factors of pyoderma and pyoderma incidence.Methods: This study used cross-sectional study design and was conducted from AugustâNovember 2013. The sample collection was done with multistage random sampling, where 196 primary school children in Jatinangor subdistrict were randomly taken to be admitted into this study. The data collection procedure consisted of physical examination and questionnaire filling. The data were statistically analyzed using independent T and chi-square test.Results: Upon examining 196 subjects, four were found with pyoderma. As such, the prevalence of pyoderma on primary school children in Jatinangor in 2013 was 2%. There was relation between personal hygiene and pyoderma incidence (p=0.041). Sex (p=0.623), healthy housing (p=0.097), socioeconomic level (p=0.742) and education level of parents (p=0.989) were not related with pyoderma.Conclusions: Personal hygiene is the risk factor that had relation with incidence of pyoderma. [AMJ.2016;3(3):434â39]Â DOI: 10.15850/amj.v3n3.867